KAJIAN INDIKATOR ASAS PROPORSIONALITAS DALAM DRIVER CONTRACT ANTARA PT GOJEK INDONESIA DAN MITRA DRIVER - Shofwatul Islamia Az Zahra; Dona Budi Kharisma (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article is to examine the indicator principle of proportionality of an electronic contract between PT Gojek Indonesia and Driver Partners. This articel is normative legal research conducted with an evaluative approach. The type of data used is secondary data which includes primary and secondary legal materials. The result shows that the characteristics of an electronic contracts based on the principle of proportionality have three aspects, namely the equal rights and obligations, the liberty in establishing the substance of the agreement, and the guarantee of rights’ implementation as well as the distribution of obligations proportionally. The identification of electronic contracts between PT Gojek Indonesia and Driver Partners resulted in the absence of the utilization of the proportionality principle. To even the rights and obligations of the parties involved, an ideal solution proposed is the enforcement of the proportionality principle in standart electronic contracts.